Ear, nose and throat disorders found in diabetic patients - Baba, Sacko Hamidou; Aminata, Kodio; Dicko, Bagayogo Hawa; Harouna, Sanogo; Dicko, Abdoul Razak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Diabetes, a non-communicable metabolic disease in perfect growth in the world, poses a problem of neurovascular dysfunction in the inner ear and the secondary immunodeficiency it causes gives a particular character to the clinical course of certain diseases of the ear, nose and throat (ENT) organs. Objective were to find out the prevalence of otorhinolaryngological disorders in patients with diabetes mellitus who presented themselves to the endocrinology and ENT departments of the Mali hospital, the diabetes center and the district hospital IV Bamako (Mali). Methods: The patients of the various departments concerned in our study, all benefited from screening consultations, we collected the data: socio-demographic, clinical and paraclinical, the management of the ENT disease and the ongoing treatment of diabetes. Results: ENT pathologies represented 2.08% of consultations of diabetic patients with a female predominance. The 46-55 age group represented 39.53%. Diabetes was type 2 in 91% of cases and fasting hyperglycemia was found in 65.12% of patients. Auditory neuropathy, influenzae rhinitis, otitis media were the common ENT diseases found in type 2 diabetics and in patients with a blood glucose greater than 1.80 gm/l. Conclusions: Diabetes, a non-communicable metabolic disease in perfect growth in the world, causes a problem of neurovascular dysfunction in the inner ear and the secondary immunodeficiency it causes gives a particular character to the clinical course of certain disorders of the ENT organs. Auditory neuropathy, influenzae rhinitis, otitis media were the common ENT diseases found in type 2 diabetics.